PENGARUH PRICE EARNING RATIO DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
The research objective is to identify and analyze the influence of Price Earning Ratioand Operating Cash Flow Return on Equity. The study object is a manufacturingcompany in Indonesia Stock Exchange (IDX). Period of observation in this studyduring the three years are: 2005, 2006, and 2007 using unbalanced pooled data.This study is a census, it is not significant either t test or F test This study usesmultiple linear regression is to look at the contribution of each independent variablein affecting stock returns. From the test results influence ratiodan price earningoperating cash flow on stock returns on companies listed in Indonesia StockExchange show that the price-earnings ratio and operating cash flows are jointlyinfluence on stock returns. Partial test results indicate that the PER negative effecton stock returns. While operating cash flow positive effect on stock returns.Keywords: price earning ratio, operating cash flow, stock return